Sajnovics’s Demonstratio (1770) A linguistic treatise based on methods of natural sciences - Constantinovitsné Vladár , Zsuzsa (Investigationes Linguisticae, 2022)
Sajnovics János (1733–1785) was the author of the basic work of comparative linguistics (Demonstratio 1770), which is considered the first scientific demonstration of the affinity of Hungarian and a Finno-Ugric language, Saami. This work was created on the occasion of the 1769 astronomical expedition in Denmark as unplanned side research. After the expedition the leader, Maximilian Hell reported on the transition of Venus (Transitio Veneris) and his assistant, János Sajnovics on the Hungarian–Lappish linguistic identity (Demonstratio).[1] This paper will deal with the scientific research methodology of Demonstratio comparing it with the methodology applied in Hell’s astronomical treatise. We also consider some contemporary critics of the methodology of Demonstratio. [1] In this paper I will use the term Lappish instead of politically correct Saami, according to the 18th-century terminology.